The Relationship Between Knowledge of Novice Nurses and The Incidence of Phlebitis In Cipto Mangunkusumo Hospital, Jakarta - Lisnadiyanti; Nursalam; Nani Asna Dewi; Akbar Hidayat (Jurnal Kesehatan Komunitas, 2022)
Background: Phlebitis leads to increased discomfort for patients, longer hospital stays, and higher healthcare costs. One of the factors causing phlebitis is the lack of skilled nurses when performing infusions. Aim: The purpose of the study was to determine the relationship between novice nurses' knowledge about infusion therapy with the incidence of phlebitis. Methods: This type of research using questionnaire to the nurse was analytic-correlational with a cross-sectional approach, with a total sample of 52 nurses who were inpatients and 54 patients who were given intravenous drip. Univariate and bivariate analyses were performed in data analysis. Results: this research showed 38.5% of nurses had poor knowledge, the incidence of phlebitis was 32.7%, and 62.8% felt comfortable with infusion. There was a significant relationship between nurses' knowledge about infusion therapy with the incidence of phlebitis (p= 0.000; = 0.05), and with quality indicators (p= 0.000; = 0.05). Conclusion: It is recommended for nurses to improve their knowledge and skills of infusion so that complications and discomfort due to infusion can be reduced.